PENGARUH FAKTOR EKSPOSI DAN TEBAL FANTOM TERHADAP MEAN GLANDULAR DOSE (MGD) PADA PESAWAT SINAR-X MAMMOGRAFI - Rauf, Resmy Aulyah; Astuty, Sri Dewi; Dewang, Syamsir; Mulyadin, Mulyadin (BERKALA FISIKA, 2020)
One of the applications of X rays in diagnostic radiology is mammography. The mammography is used for detecting abnormalities in the breast tissue early with the ability to detect microcalcification (<5 mm). Unlike the conventional X-ray and CT scanner, the clinical mammography uses a low voltage <35 kVp, because the properties of the breast tissue structures are soft and thin. Although the tube voltage source is relatively low, in clinical use, the absorbed dose by patients in the form of mean glandular dose (MGD) must be lower than the value standards had been established by the Nuclear Energy Supervisory Agency (BAPETEN) No.2, 2018, i.e <3 mGy. This study aims to evaluate the effect of variations in the values of the tube voltage, the current-time, and the thickness of the polymethyl-methacrylate (PMMA) phantom on the calculation results of the MGD values. The results obtained showed that the mean MGD values for the 4,5 cm of the phantom thickness were 0.077, 0.087, and 0.093 mGy (at 4.5 mAs) and 0.171, 0.194, and 0.207 mGy (at 10 mAs), while for the 6 cm phantom thickness obtained 0.103, 0.117, and 0.124 mGy (at 4.5 mAs) and 0.228, 0.259, and 0.276 (at 10 mAs) for all the data to 27, 28, and 29 kVp of tube voltage, respectively. All of the MGD values obtained about between 0.077-0.276 mGy are <3 mGy or still under BAPETEN standards.Keywords: mammography, MGD value, PMMA phantom